2021
DOI: 10.1111/bju.15647
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine cells in prostate cancer correlate with poor outcomes: a systematic review and meta‐analysis

Abstract: To perform a systematic review and meta-analysis of the literature to understand the variation in the reporting of neuroendocrine staining and determine the influence of reporting neuroendocrine staining at diagnosis on patient outcomes. MethodsMedical databases were searched to identify studies in which adenocarcinoma specimens were stained with any of the following four neuroendocrine markers: chromogranin A (CgA), neuron-specific enolase (NSE), synaptophysin and CD56. The prevalence of neuroendocrine staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…In a recent systematic review, Kannan et al have evaluated the role of CgA IHC in patients with PCa. 18 response to androgen deprivation therapy due to the absence of the androgen receptor in neuroendocrine cells resulting in a poor prognosis for these patients. Moreover, it has been suggested that neuroendocrine differentiation may be one of the many mechanisms behind castration-resistant development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent systematic review, Kannan et al have evaluated the role of CgA IHC in patients with PCa. 18 response to androgen deprivation therapy due to the absence of the androgen receptor in neuroendocrine cells resulting in a poor prognosis for these patients. Moreover, it has been suggested that neuroendocrine differentiation may be one of the many mechanisms behind castration-resistant development.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has been performed in a selected cohort of patients with localized/locally advanced disease with negative IHC and therefore the results apply to the enrolled population. In a recent systematic review, Kannan et al have evaluated the role of CgA IHC in patients with PCa 18 . According to their results CgA IHC may vary between 4% and 100% underlying the high variability of CgA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely accepted that the early diagnosis (An et al, 2021;Kannan et al, 2021) of tumors is essential for achieving a better prognosis and a lower mortality rate. Accurate diagnostic biomarkers (Ott et al, 2009;Wardle et al, 2015;Dragani et al, 2020) for detecting early-stage tumors are of great clinical significance.…”
Section: Duxap10 As a Diagnostic And Prognostic Biomarkermentioning
confidence: 99%
“…And poor quality of life, especially cancer (Lee et al, 2018;Moliner et al, 2019;Sidney et al, 2019;Mulder et al, 2021;Su et al, 2021). Cancer (Mohsen et al, 2014;Christensen et al, 2018;Kannan et al, 2021;Mokgautsi et al, 2021) has become one of the most common causes of death worldwide, and the identification of cancer-related targets and relevant carcinogenesis mechanisms for patients at the early stage of the disease are urgently needed (Saha et al, 2019;Jiang et al, 2020;Brennan and Smith, 2021;Hua et al, 2021;Jones et al, 2021).…”
Section: Introductionmentioning
confidence: 99%